Réponse :
Explications étape par étape
Bonjour
Developper :
A = 8(3a - 7)
A = 24a - 56
b) calculer A pour a = -1 :
A = 24 * -1 - 56
A = -24 - 56
A = -81
Developper :
B = 3x(5x - 2) - (8x - 7)
B = 15x^2 - 6x - 8x + 7
B = 15x^2 - 14x + 7
b) calculer B pour x = 5 :
B = 15 * 5^2 - 14 * 5 + 7
B = 15 * 25 - 70 + 7
B = 375 - 63
B = 312
Developper :
C = (3x - 2)(-3x - 7)
C = -9x^2 - 21x + 6x + 14
C = -9x^2 - 15x + 14
b) calculer C pour x = 1/3 :
C = -9 * (1/3)^2 - 15 * 1/3 + 14
C = -9/9 - 15/3 + 14
C = -1 - 5 + 14
C = -6 + 14
C = 8